A Comparison of Vibration Magnitudes on the Tool with Different Subject According to the ISO 8662-7 Standard - NAKAGAWA, Yoshiyuki; SHIDA, Yoshichika; OKUNO, Masaomi; YONEKAWA, Yoshiharu; MAEDA, Setsuo (Industrial Health, 2001)
Recently, ISO has defined the guidelines for the evaluation of the measurement and exposure limits of hand-transmitted vibrations at the handle of hand-held portable power tools. In a measurement of vibrations at pneumatic impact wrenches that tighten and remove screws. ISO 8862-7 standard: 19971) and ISO 5349 standard: 19862) are set as international standards. In order to make an exact measurement of the quantities of vibrations exposed to the hand-arm system of a human body, ISO 8662-7 gives specifications to a measurement device and a loading device. As to a measurement device, for instance, the mass, installation method etc. of transducers and mechanical filters are defined. In addition, it specifies with each tolerance the working conditions of a pneumatic tool, the number of revolutions of socket in a loading device, the feed force, the number of subjects, and such an evaluation method as how to decide a declaration value of vibrations. These specifications give toolmakers a comparative measurement of vibration values of their tools before shipment. Meanwhile, although the measurement condition described in ISO8662-7: 1997 is that skilled operators conduct vibration measurement, no provisions as to operators are made in detail. Hence, this study focuses its concern on ambiguous work experience years in measuring vibrations of the tools in conformity with ISO 8662-7, and hereby the effect of years of work experience upon measurement values is considered and at the same time a knowledge of how to select operators is made clear.